PERENCANAAN LANSKAP TEPIAN LINTASAN KERETA (Studi Kasus : Jalur Pasar Minggu – Gambir, Propinsi DKI Jakarta) - Artitya Artitya; Siti Nurisjah; Heny Suharsono (Jurnal Lanskap Indonesia, 2010)
The purpose of this landscape planning for railway  zone was giving a sense of amenity, tranquility, beauty, and visual harmony for the train users as well as for the environment and people surround it.This planning was made based on problem analisys that occurs on the site. This problems consists of land use that influencing physical, social-economical, and technical aspect, cross road that influencing phisycal and technical aspect, and noise that influencing physical and technical aspect.In the end, the form of this site planning will be  handed in detailed models based on the type of each problem occurred.